Enhanced Anti‐Tumour Efficacy of iRGD‐Modified Cell‐Bound Membrane Vesicles (iRGD‐CBMVs) as a Novel Drug Carrier - Haonan Zhao; Zhendong Huang; Qinghua Sheng; Wenxiang Shao; Min Zeng; Kun Wang; Yang Zhang; Ying Qin; Zhihao Xiong; Lizhen Chen; Huaying Wang; Tong Rong; et al. (Journal of Extracellular Biology)
ABSTRACT Cancer continues to be the foremost cause of mortality in humans. Persistent challenges in cancer treatment include inadequate drug targeting, severe toxicological side effects and uncontrolled drug distribution. The bioinspired membrane vesicle drug delivery systems have been emerging as promising therapeutic strategies. This study characterises unique cell‐bound membrane vesicles (CBMVs), which are impervious to standard cleaning agents and effectively loaded with doxorubicin (DOX). For the first time, we used iRGD peptide to modify the CBMVs to enhance the CBMVs' targeting capabilities for cancer cells. Laser confocal microscopy and 1H Nuclear Magnetic Resonance Spectra (1H NMR) have confirmed the CBMVs' iRGD modification and effective encapsulation with DOX (iRGD‐CBMVs‐DOX). Then, we used the iRGD‐CBMVs‐DOX to treat tumour cell lines and tumour‐bearing mouse models. Our research identified that iRGD‐CBMVs‐DOX proves effective in inhibiting cell growth and migration for tumour cell lines, significant anti‐tumour ability, reduced organ toxicity and continuous drug administration were revealed in tumour‐bearing mouse models. Additionally, the iRGD‐CBMVs‐DOX demonstrated sustained drug release, indicating their potential for prolonged circulation. These findings are pivotal in enhancing cancer treatment through novel nanomedicine strategies, and highlight the potential of iRGD‐modified vesicles (e.g., iRGD‐CBMVs) as efficient drug carriers, contributing to targeted and biocompatible drug delivery advancements for cancer treatment.